VALUE-BASED HUMAN RESOURCE MANAGEMENT IN THE CONTEXT OF ENSURING INVESTMENT SUSTAINABILITY OF AN ENTERPRISE - Харковина, О.Г.; Манухіна, М.Ю. (Управління змінами та інновації, 2024)
The article explores the role of value-based human resource management as a key factor in ensuring the investment sustainability of enterprises amid socio-economic transformation. It is substantiated that effective HR management grounded in modern value orientations contributes to increasing investor confidence, enhancing employee motivation, and strengthening the internal capacity of enterprises for sustainable development. The paper highlights the contrast between management models shaped under state paternalism and those rooted in economic liberalism, which dominate current market conditions. The evolution of the managerial function is analyzed – from administrative control to professionalized managerial autonomy – within the framework of managerialism focused on achieving economic efficiency. The study addresses issues of responsibility for human resources, changing management styles, social attitudes of personnel, and the value systems that shape labor behavior. Special emphasis is placed on the interconnectedness of labor and consumer behavior, the quality of life, and the level of subjective well-being of employees. A practical approach is proposed for assessing the socio-psychological attitudes of staff based on the concept of dispositional regulation of behavior. The research results provide opportunities to enhance enterprise HR policies, develop more effective motivation systems, increase employee engagement, and adapt management decisions to the dynamic shifts in values. A functional model of HR management responsibilities at different levels is proposed, incorporating both strategic vision and practical tools for influencing personnel behavior. The authors emphasize the necessity of implementing new social technologies in HR management aimed at creating a favorable value climate within the organization. The article also considers the challenges of formulating a corporate mission in the context of shifting social orientations and generational differences in employee value systems. It is concluded that value-based human resource management is not only a driver of workforce efficiency but also a crucial element in maintaining the long-term investment appeal of enterprises.